2018
DOI: 10.1080/03009742.2018.1459831
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic risk factors and the incidence and progression of radiographic hand osteoarthritis: a population-based cohort study

Abstract: Overall metabolic risk factors were not independently or collectively associated with greater amounts of radiographic hand OA incidence or progression over 7 years, but diabetes was associated with radiographic progression in nodal, and possibly generalized and erosive OA. Diabetes has previously been associated with prevalent but not incident hand OA. Further investigation in hand OA subsets using objective measures accounting for disease duration and control is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 51 publications
1
28
3
1
Order By: Relevance
“…The compound metabolic syndrome showed a none significant tendency to increase osteoarthritis of both hips. These results are partially in line with previous studies which show that most singular components of metabolic syndrome as well as the compound metabolic syndrome have no impact on osteoarthritis of the hip joints [10,27,28], whereas other studies have shown, that prevalence of metabolic syndrome is higher in patients with osteoarthritis [29]. It has to be acknowledged, that most studies showing a positive association between metabolic syndrome or its singular components (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…The compound metabolic syndrome showed a none significant tendency to increase osteoarthritis of both hips. These results are partially in line with previous studies which show that most singular components of metabolic syndrome as well as the compound metabolic syndrome have no impact on osteoarthritis of the hip joints [10,27,28], whereas other studies have shown, that prevalence of metabolic syndrome is higher in patients with osteoarthritis [29]. It has to be acknowledged, that most studies showing a positive association between metabolic syndrome or its singular components (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Risk factors which increase the chance of IPJ osteoarthritis progression in patients have been studied in the literature. We identified eight studies (seven high risk of bias) investigating potential risk factors for the progression of finger IPJ osteoarthritis [37][38][39][40][41][42][43][44]. All studies measured osteoarthritis progression radiographically, using a version of the KL classification system [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Results were largely similar when DIPJ and PIPJ osteoarthritis when assessed separately. The KL classification system [45,46] was used to measure osteoarthritis progression by all studies [37][38][39][40][41][42][43][44]49]. The KL classification system [45,46] is a sensitive method for measuring the progression of radiographic hand osteoarthritis over a 1-year time frame [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations